THE CONCEPT OF ARAB ISLAMIC CIVILIZATION IN THE EYES OF THE ENGLISH ORIENTALIST DONALD HILL ANWAR ABDUL-JABBAR MUHAMMAD - Bakr, Qahtan Adnan (International Journal of Psychosocial Rehabilitation, 2020)
The Arab-Islamic civilization is considered one of the important pillars upon which the Islamic Arab state was built since its foundation during the era of the Muhammadiyah message and continued with it, taking the feature of development, which Hill spoke about until the end of the Abbasid era, as he considered that the sustainability of the Arab community depends entirely on it, and for this we will address the most important opinions taken by him in this regard.